Some aspects of the grammar of the Eskimo dialects of Cumberland Peninsula and North Baffin Island - Harper, Kenn (Mercury series., 1974)
An analysis of the grammar of the two dialectal areas. Appendices discuss the historical background and give a critique of the syllabic orthographic system used by Eskimos of the eastern arctic.